Evaluation of damping reduction factors for estimating elastic response of structures with high damping. - Lin, Yu-Yuan
The damping reduction factors are used in a few building codes in order to estimate the elastic response spectrum with high damping ratios from its 5 percent damped counterpart. At present, much research regarding this factor has been published. The purpose of this paper is to evaluate the accuracy of five different models of damping reduction factors. In addition, the damping reduction factors adopted in the recent U.S.A. seismic codes are also evaluated. Statistical studies are carried out according to a total of 216 earthquake ground motions recorded on firm sites in California. Considered here are elastic single-degree of freedom (SDOF) systems with natural vibrating periods between 0.1 and 6.0 s. Mean ratios and dispersion of approximate to exact maximum elastic displacement demands corresponding to various damping reduction factors are computed as functions of the natural vibrating period and the viscous damping ratio.
Keywords: Damping reduction factors; Evaluation; Elastic displacement responses of structures with high damping